Healthy Sport Parenting: Upaya Orang Tua dalam Meningkatkan Kualitas Kesehatan dengan Membiasakan Aktivitas Fisik pada Anak Tunagrahita - Rizqi Fajar Pradipta; Taufik, Taufik; Wiwik Dwi Hastuti (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Based on the findings when conducting interviews with the principal of the BC Kepanjen SLB school, it was found that as many as 60% of students and female students with intellectual disabilities had poor lifestyles, such as consuming food that did not have good nutrition, snacks on the sidelines of school, and it was difficult for them to be invited to do physical activity. teachers, are still too dependent on other people in carrying out any activity. Based on these problems, the right solution for partners is the Healthy Sport Parenting program, a parent learning program to improve the quality of health for children with intellectual disabilities. This program focuses on learning for parents, namely self-care for children with intellectual disabilities, learning what physical activities and sports are suitable for children with intellectual disabilities. The output target has been achieved from this program, namely that parents or guardians can implement and teach physical activities and sports to children with intellectual disabilities.